(tan A t cotA) sinA cosA =1
Answers
Answered by
1
Answer:
Step-by-step explanation:
L.H.S=(1+cotA+tanA)(sinA−cosA)
=(sinA+sinAcotA+tanAsinA−cosA−cosAcotA−tanAcosA)
=(sinA+
sinA
sinAcosA
+tanAsinA−cosA−cosAcotA−
cosA
cosAsinA
)
=(sinA+cosA+tanAsinA−cosA−cosAcotA−sinA)
=tanAsinA−cosAcotA
=sinAtanA−cotAcosA=R.H.S
Proved.
Answered by
2
Step-by-step explanation:
that is the answer pls follow me
Attachments:
![](https://hi-static.z-dn.net/files/d61/9d465e623eae81329d846b6462a6f879.jpg)
Similar questions